Giant Petroclival Primary Intradural Chordoma: Case Report and Systematic Review of the Literature - AlOtaibi, Fahad; Guiot, Marie-Christine; Muanza, Thierry; Maio, Salvatore Di (Journal of Neurological Surgery Reports, 2014)
Background Chordomas are rare, locally aggressive neoplasms thought to arise from notochordal remnants in the axial skeleton. Primary intradural chordomas are considered to be extremely rare. In this article a giant intradural petroclival chordoma is presented, and a synthesis of the available literature is performed to measure overall survival (OS) and recurrence-free survival (RFS) and to identify prognostic factors.Methods A systematic Medline review yielded 47 patients with purely intradural tumors from 38 publications including 39 chordomas, 8 cases of ecchordosis physaliphora, and 1 case with features of both. The 5-year OS and RFS were calculated based on the Kaplan-Meier method. Risk factors for progression or mortality were analyzed using binomial logistic regression.Results Maximal tumor diameter varied from 1.5 to 6.0 cm (mean: 3.2 cm). Tumors were located predominantly in the prepontine area (66.7%). Combined 5-year Kaplan-Meier OS and RFS were 77% ± 11% and 74% ± 11%, respectively. Incomplete surgical resection, larger tumor diameter, and an elevated Ki-67 index were statistically more frequent in cases of recurrence and mortality.Conclusions Based on a systematic literature review, the behavior of primary intradural chordomas may be closer to typical chordomas than was previously thought.
Keywords: chordoma; notochord; skull base neoplasms; brainstem neoplasms